Flower morphology, flower color, flowering and floral fragrance in Paeonia L. - Fan, Yongming; Jin, Xing; Wang, Mengshan; Liu, Huadong; Tian, Weili; Xue, Yandong; Wang, Kai; Li, Hu; Wu, Yan (Frontiers in Plant Science, 2024)
Paeonia have diverse flower colors, rich flower types, varying bloom periods, and delightful fragrances, rendering them highly valuable for both ornamental and economic purposes in horticulture. Investigating the developmental mechanisms of morphology, flower color, flowering and floral fragrance in Paeonia holds significant value for enhancing their ornamental traits and conducting germplasm improvement. This review provides an overview of research progress on Paeonia flower morphology (including flower bud differentiation, classification, omics applications in shape studies, and functional genes regulating flower morphology), flower colors (omics applications in color research and functional genes regulating flower colors), bloom periods (flower bud dormancy, flowering time), and fragrances (preparation, analysis, components, and molecular biology research of flower fragrances) within the Paeonia. Additionally, it offers a comprehensive analysis of current research challenges and future directions.